Utilization of environmentally friendly essential oils on enhancing the postharvest characteristics of Chrysanthemum morifolium Ramat cut flowers - Iman Mohamed El-Sayed; Rasha Ahmed El-Ziat (Heliyon, 2021)
Chrysanthemum is one of the most consumed and most valuable cut flowers worldwide. In this study, the effectiveness of three concentrations of either thyme oil (300,400 and 500 mg/l) or clove oil (150,250 and 500 mg/l) as additives in holding the postharvest solutions of chrysanthemum ‘‘Arctic Queen White’’ cut flowers were investigated. The experiments were carried out as a completely randomized design in three replicates. Many postharvest characteristics have been evaluated, such as the vase life of cut flowers, diameters of head flowers and stem, dry matter of flowers, total vase water uptake, total loss of water, relative fresh weight. Additionally, the chlorophyll contents, total sugar, and bacterial counts were determined. The results showed that the longest vase life of cut chrysanthemum was 36.50, 33.40 days, and 35.88, 31.33 days by addition of either the thyme oil (500 mg/l) or clove oil (250 mg/l) in holding solution as compared with distilled water (18.09 and 17.22 days) in both seasons. The highest total vase water uptake and relative fresh weight were (225.00, 211.05 g/flower/day) and (79.89, 70.37 %) of cut chrysanthemum treated with 500 mg/l thyme oil in both seasons. Whereas the lowest total water loss in the two seasons was 155.11 and 156.60 g/flower/day was found with 400 mg/l thyme oil. The greatest chlorophyll a, b, carotenoids, and total sugar contents obtained from treated cut chrysanthemum with 500 mg/l thyme oil (6.89, 2.37, 5.99 mg/g, and 0.88 mg/gm D.W, respectively). Furthermore, the treatment of cut flowers with selected oils has significantly decreased the bacterial growth compared to the control. Whereas the minimum bacterial activities were <1 C.F.U/ml with cut chrysanthemum fortified with 500 mg/l thyme and clove oils. Moreover, the superlative treatments with thyme (500 mg/l) and clove (250 mg/l) showed a prime state of xylem vessels comparable with the control.thus, the usage (addition) of thyme and clove oils as a natural preservative in holding solutions instead of ...